Cucumber Economic Values and Its Cultivation and Breeding 2021
DOI: 10.5772/intechopen.96393
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Principle in Cucumis sativus L.

Abstract: Diabetes is one of the leading cause of death globally. One of the strategies towards managing diabetes is the antidiabetic drugs which has recorded a huge success but accompanied with different degrees of side effect, hence, the use of natural plants products is encouraged. Several reports of antidiabetic medicinal plants have flooded literature but few has led to identification of active ingredient in such. Cucumis sativus is one of such plants reported to have antidiabetic property but there is little or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Kaempferol has anti-inflammatory, anti-cancer, and anti-diabetic properties, which protect the liver and prevent metabolic diseases. Kaempferol has been reported to lower blood sugar and inhibit alpha-amylase and alpha-glucosidase (two carbohydrate-hydrolyzing enzymes found in the digestive tract) (25). Ibitoye et al showed that kaempferol isolated from cucumber inhibits alpha-amylase and alpha-glucosidase enzymes with anti-diabetic properties and hypoglycemic and antioxidant activities (26).…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferol has anti-inflammatory, anti-cancer, and anti-diabetic properties, which protect the liver and prevent metabolic diseases. Kaempferol has been reported to lower blood sugar and inhibit alpha-amylase and alpha-glucosidase (two carbohydrate-hydrolyzing enzymes found in the digestive tract) (25). Ibitoye et al showed that kaempferol isolated from cucumber inhibits alpha-amylase and alpha-glucosidase enzymes with anti-diabetic properties and hypoglycemic and antioxidant activities (26).…”
Section: Discussionmentioning
confidence: 99%
“…3 They are also rich in flavonoids and polyphenols that exhibit antidiabetic activity. 4 The fruits of Cucumis trigonus contain steroid and triterpenoid compounds, cucurbitacin B and proteolytic enzymes and it showed analgesic and anti-inflammatory activities. C. prophetarum has also been testified to have various biological activities as abortifacient and antihepatotoxic in the treatment of liver diseases.…”
Section: Introductionmentioning
confidence: 99%